Washback on national examination: English language teacher and student’s perception - Minkhatunnakhriyah; Tati Rohayati (TRANSBAHASA, 2020)
Washback refers to influences of testing on teaching and learning for example from National Examination which is a test to evaluate and measure the student's competence nationally by the government after through process of teaching learning. This study attempts to investigate the perception EL teachers and students on washback of National Examination (NE). The participants of this study were ninth grade of junior high school in Jakarta, it will be taken four students from each class and English teachers. This study uses questionnaires and interviews to collect the data and the research method of this study used was a descriptive qualitative method. The result from this study show that the students’ and teacher perception on ENE provide them negative and positive washback. Furthermore, the positive washback from ENE provide several aspects such as the teacher teach English subject more specific in certain skill and its effective to the students. However, the negative washback shown in several side likes the national Examination especially English subject just give the students feel anxiety because they need extra time to do the questions of national examination exercise and feel unfair for passed the standard test of school determine by national examination which conducted only three days.